Multidrug-Resistant, Including Extended-Spectrum Beta Lactamase-Producing and Quinolone-Resistant, Escherichia coli Isolated from Poultry and Domestic Pigs in Dar es Salaam, Tanzania - Kimera, Zuhura I. (Antibiotics (Basel), 2021)
We determined the phenotypic profile of multidrug-resistant (MDR) Escherichia coli isolated from 698 samples (390 and 308 from poultry and domestic pigs, respectively). In total, 562 Enterobacteria were isolated. About 80.5% of the isolates were E. coli. Occurrence of E. coli was significantly higher among domestic pigs (73.1%) than in poultry (60.5%) (p = 0.000). In both poultry and domestic pigs, E. coli isolates were highly resistant to tetracycline (63.5%), nalidixic acid (53.7%), ampicillin (52.3%), and trimethoprim/sulfamethoxazole (50.9%). About 51.6%, 65.3%, and 53.7% of E. coli were MDR, extended-spectrum beta lactamase-producing enterobacteriaceae (ESBL-PE), and quinolone-resistant, respectively. A total of 68% of the extended-spectrum beta lactamase (ESBL) producers were also resistant to quinolones. For all tested antibiotics, resistance was significantly higher in ESBL-producing and quinolone-resistant isolates than the non-ESBL producers and non-quinolone-resistant E. coli. Eight isolates were resistant to eight classes of antimicrobials. We compared phenotypic with genotypic results of 20 MDR E. coli isolates, ESBL producers, and quinolone-resistant strains and found 80% harbored blaCTX-M, 15% aac(6)-lb-cr, 10% qnrB, and 5% qepA. None harbored TEM, SHV, qnrA, qnrS, qnrC, or qnrD. The observed pattern and level of resistance render this portfolio of antibiotics ineffective for their intended use.